A new structure of a wide band bridge power limiter - Khalifa Echchakhaoui; Elhassane Abdelmounim; Jamal Zbitou; Hamid Bennis (Institute of Advanced Engineering and Science, 2020)
In this work, new design and simulation of a microstrip power limiter based on Schottky diode is presented. The proposed circuit is a zero bias power limiter built by associating a transmission line in parallel to a four Schottky rectifier bridge circuit. The first circuit using a single stage rectifier is analyzed and simulated. To improve this single stage, a second and final limiter is designed with two stages rectifier. Simulation results for the final circuit show an ideal limiter behavior and good performance of limiting rate up to 20dB for a threshold input power varying from 5 dBm to 30 dBm. While insertion loss remains low at small signal.